2008
DOI: 10.1111/j.1365-2559.2008.03082.x
|View full text |Cite
|
Sign up to set email alerts
|

hCGβ expression by cervical squamous carcinoma –in vivo histological association with tumour invasion and apoptosis

Abstract: hCG beta expression correlates with reduced tumour cell apoptosis and may be involved in tumour vascularization and dissemination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…This data is considered rather controversial. New data, however, seemingly confirms these findings in cervical cancer cells [99]. Other studies indicate a clear association between detection of free β-subunit in serum samples, or detection of its degradation product, β-subunit core fragment, in urine samples, with cases with poor grade and advanced stage cancer, or poor outcome malignancy [100-103].…”
Section: Biological Function Of Free β-Subunitmentioning
confidence: 79%
See 1 more Smart Citation
“…This data is considered rather controversial. New data, however, seemingly confirms these findings in cervical cancer cells [99]. Other studies indicate a clear association between detection of free β-subunit in serum samples, or detection of its degradation product, β-subunit core fragment, in urine samples, with cases with poor grade and advanced stage cancer, or poor outcome malignancy [100-103].…”
Section: Biological Function Of Free β-Subunitmentioning
confidence: 79%
“…These studies together indicate that expression of free β-subunit leads to a negative outcome in human malignancies. Multiple reports now indicate that free β-subunit may have a specific role in malignant transformation of cells [97,99,105-109]. In these, and other studies, stimulation of malignant cell growth has been demonstrated by the action of free β-subunit [97,99,105-109].…”
Section: Biological Function Of Free β-Subunitmentioning
confidence: 96%
“…They demonstrated the presence of the β subunit in metastatic malignancies in vivo [63] as well as in cultured cancer cells in vitro [64]. Other groups have confirmed this is cervical cancer and other cancers [6567]. …”
Section: Biological Actionsmentioning
confidence: 99%
“…Both hyp-hCG and the β-subunit has been shown to act through the TGFβ receptor, and it is hypothesized that this occurs via similar pathways [6]. The application of hCG-β as a prognostic marker of poor prognosis in cancer is being examined in multiple tumor paradigms including cervical, vaginal, endometrial and bladder [65, 7173]. These studies collectively indicate that the expression of the free β-subunit invokes a negative outcome in human malignancies.…”
Section: Biological Actionsmentioning
confidence: 99%
“…Slides were stained using standard immunohistochemistry (IHC) methods published elsewhere [32] . In brief, paraffin embedded tissue blocks were cut into 6μm sections, dewaxed and rehydrated through graded alcohol to water.…”
Section: Methodsmentioning
confidence: 99%